Cost-effectiveness analysis and safety of erythromycin 4% gel and 4% chlorhexidine scrub for pitted keratolysis treatment - Charussri Leeyaphan (2020)
© 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group. Background: Studies of Pitted keratolysis (PK) treatment are limited. Objectives: To study cost-effectiveness and to compare the safety of 4% chlorhexidine scrub with 4% erythromycin gel, for PK infections. Materials and methods: This cohort study was conducted on naval rating cadets with a clinical diagnosis of PK at Chumpol Naval Rating School, Thailand in 2016. Participants were randomly treated with either 4% erythromycin gel or 4% chlorhexidine scrub for 4 weeks. The clinical examinations were evaluated at the baseline and at 1 and 2 months after treatment. A decision-tree model was used to evaluate the costs, resource utilization and outcomes as quality-adjusted life-years (QALYs). Results: Of 344 naval rating cadets, 125 (36.3%) were diagnosed with PK. Sixty-four were treated with erythromycin. Approximately 80% of participants had complete resolution Foot odor were significantly improved at 2 months (p <.001) for both groups. No adverse effects were reported. Total cost for 4 weeks’ treatment with the erythromycin gel and chlorhexidine scrub was US$77.34, US$51.9, respectively. Chlorhexidine treatment and erythromycin gel had 0.1526 and 0.1425 QALYs, respectively. Conclusions: treatment of PK with either 4% chlorhexidine scrub or 4% erythromycin gel had similar outcomes. However, using chlorhexidine scrub was more cost-effective.